The importance of Social Networks as a marketing tool to increase competitive advantage in an IES in Juazeiro do Norte - CE (Research, Society and Development, 2021)
The new economic and commercial dynamics of the globalized world impose on the business market all over the world a series of changes and adaptations by the beginner in search of techniques that not only accompany, but, above all, make a difference in a competitive commercial context. Thus, the internet and so-called media or social networks has been an important market, attracting interest, given its facilities for interacting with consumers, lately revising a potential market that already contains a large number of investors moving a small amount of capital. The present work studies the development of digital marketing in recent years in Brazil and more specifically its development in social networks or media in an IES - Private Higher Education Institution in Juazeiro do Norte - CE. It was then used a research instrument already done for a company and paid / adapted in an organization in an HEI in order to identify the work done with social media in the company. This is a descriptive research, which includes a case study. An interview was made with an IES employee, in charge of the IT activities sector responsible for monitoring the networks. It was verified and verified that the HEI is on the right path in relation to working with social networks, dedicating time and working with contact with the student, but avoiding the need for greater IT interaction with the Marketing and Communication area IES to work together to communicate efficiently and effectively.